Cinnamon extract on the characteristics of ruminal fermentation in in-vitro systems - Vega-Zuñiga, Miguel Angel; Vázquez-Armijo, José Fernando; Martínez-González, Juan Carlos; Quintanilla-Medina, Jairo Jeú; Lucero-Magaña, Froylán Andrés; López-Aguirre, Daniel (Ecosistemas y Recursos Agropecuarios, 2021)
Two experiments were conducted to evaluate the effect of cinnamon extract (Cinnamomum verum) in a lamb ration on fermentation parameters and ruminal degradability. In the first experiment, the technique of in vitro gas production (PG) was carried out to a ration for lambs added with 0.0, 0.6, 1.2 and 1.8 mL g-1 of DM of C. verum extract. In the second experiment, the technique of in vitro ruminal degradability of dry matter (DMD) and fiber fractions (NDFD and ADFD) of a lamb diet added with an extract of C. verum was carried out in different incubation times. The addition of the extract showed linear and quadratic (p < 0.01) effects on the PG asymptote (b). The addition of C. verum extract had linear (p < 0.01) effects on IVDMD. The DMD at 24 and 48 h incubation showed no difference between treatments. The NDFD was lower (p < 0.01) at 72 h when adding C. verum extract versus the control treatment, but there were no significant effects at 24 and 48 h. The ADFD of the control treatment versus C. verum extract was significant (p < 0.05) at 24 and 72 h. In conclusion, C. verum extract modifies the parameters of ruminal fermentation and reduces the degradability of fiber at the end of ruminal fermentation.